2016
DOI: 10.1542/peds.2015-3994
|View full text |Cite
|
Sign up to set email alerts
|

Learning Problems in Children of Refugee Background: A Systematic Review

Abstract: CONTEXT: Learning problems are common, affecting up to 1 in 10 children. Refugee children may have cumulative risk for educational disadvantage, but there is limited information on learning in this population. OBJECTIVE:To review the evidence on educational outcomes and learning problems in refugee children and to describe their major risk and resource factors. RESULTS:Thirty-four studies were included. Refugee youth had similar secondary school outcomes to their native-born peers; there were no data on presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(114 citation statements)
references
References 55 publications
6
94
0
14
Order By: Relevance
“…The term “transition” is particularly appropriate to describe their experiences because it usually involves physically relocating from their country of origin, adapting to a new culture, language and education system, and transitioning from New Arrival Programs (NAP) or Intense English Language Programs (IELP) to mainstream schools, and from full‐time education to the world of work (Hugo et al, ). Other common challenges include limited literacy in the mother tongue, limited or interrupted former education, unfamiliarity with the education system, lack of parental literacy and education, limited parental involvement in and support for their education, low teacher expectations, and racism (Graham, Minhas, & Paxton, ; Hatoss, O'Neill, & Eacersall, ; Sainsbury & Renzaho, ). There is also some indication that parents and teachers do not always agree on educational methods and pathways ( Graham et al, ).…”
Section: Study Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term “transition” is particularly appropriate to describe their experiences because it usually involves physically relocating from their country of origin, adapting to a new culture, language and education system, and transitioning from New Arrival Programs (NAP) or Intense English Language Programs (IELP) to mainstream schools, and from full‐time education to the world of work (Hugo et al, ). Other common challenges include limited literacy in the mother tongue, limited or interrupted former education, unfamiliarity with the education system, lack of parental literacy and education, limited parental involvement in and support for their education, low teacher expectations, and racism (Graham, Minhas, & Paxton, ; Hatoss, O'Neill, & Eacersall, ; Sainsbury & Renzaho, ). There is also some indication that parents and teachers do not always agree on educational methods and pathways ( Graham et al, ).…”
Section: Study Aimsmentioning
confidence: 99%
“…Other common challenges include limited literacy in the mother tongue, limited or interrupted former education, unfamiliarity with the education system, lack of parental literacy and education, limited parental involvement in and support for their education, low teacher expectations, and racism (Graham, Minhas, & Paxton, ; Hatoss, O'Neill, & Eacersall, ; Sainsbury & Renzaho, ). There is also some indication that parents and teachers do not always agree on educational methods and pathways ( Graham et al, ).…”
Section: Study Aimsmentioning
confidence: 99%
“…also mention a Canadian study of 91 refugee youth from nine countries. This study determined that “younger age at migration, greater length of time since resettlement, and urban residence were associated with better secondary school outcomes” (Graham et al., , p. 8). Furthermore, Sudanese youth reported that challenges with the English language were a common barrier to success.…”
Section: Classroom Strategies For El Students With Previous Traumamentioning
confidence: 99%
“…Even more shocking, over half of these refugees, or people seeking asylum, are children. Graham et al (2016) closely examined 34 full-text articles to compile data about learning outcomes and potential problems in refugee children. It was concluded that "internalizing problems" (i.e., anxious, depressive, and overcontrolled behavior) were more common than "externalizing problems"(i.e., aggressive, hyperactive,noncompliant, and undercontrolled behavior) (p. 7).…”
Section: Previous Traumamentioning
confidence: 99%
“…A large body of research indicates that children with refugee and asylum seeker backgrounds living in resettlement countries such as Australia are vulnerable to psychological distress resulting from the cumulative stressors that occur during pre-migration, migration, and resettlement (Graham, Minhas, & Paxton, 2016;Henley & Robinson, 2011). These stressors may include exposure to war and violence, changes to family dynamics, and shifting social and cultural expectations, and there may be differences based on visa status, especially in relation to the uncertainty of temporary visas (Fazel, Reed, Panter-Brick, & Stein, 2012).…”
Section: Introductionmentioning
confidence: 99%